Optimización del sistema de tendido de cable de fibra óptica de la empresa Ever Bustamante Telecomunicaciones de la ciudad de Cartagena. (2023)
The objective of this project was to optimize the fiber optic cable laying system of the Ever Bustamante Telecomunicaciones (EBT) company, seeking to improve time management and the workforce in charge of laying the cabling that is installed through the channelized network system and aerial. This procedure was carried out manually by the EBT company, a fiber optic infrastructure construction services company in the city of Cartagena. EBT had been developing some activities in a rudimentary way that required a lot of time and personnel at the time of installing the fiber optic cabling. With this project, the manual cable laying process carried out with a low-capacity motor, which did not exert the force required by the laying system, was improved. For this, the capacity of the motor was increased, and an automatic control system was also proposed by means of a controller and a measurement system and an actuator, which will lead to reducing breakdowns generated by mishandling on the part of the personnel, also when carrying out tests with The updated equipment showed a greater productive capacity in less time and better administration of the human resources that perform the laying tasks. The foregoing optimized the financial resources of the company, since the laying methods used previously generated significant administrative cost overruns for the company, which is in a process modernization stage.